The Effect Of Learning Quality, Service Quality, And Promotion on Decission To Choose School At SDIT Mutiara Rahmah Balikpapan - Fitriana Fitriana; Khairun Nisa Agustin (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study aims to determine the effect of the independent variables, namely Quality of Learning (X1), Quality of Service (X2), and Promotion (X3), on the dependent variable, namely Decision to Choose (Y) at SDIT Mutiara Rahmah Balikpapan. Design/methodology/approach: This study uses a non-probability sampling technique using a sample of 200 respondents. Data collection techniques are questionnaires, observations, interviews. Findings: Based on the results of multiple regression analysis, the correlation coefficient (R) was obtained. From the results of multiple linear regression analysis, the R value was 0.663 and the determinant R Square value (R2) was 0.401. The F_count value obtained is 43,649. This value is far above the F_table value of 2.65 with a significance level of = 0.000 which is far from 0.05. Research limitations/implications: Thus, it can be concluded that the variables of learning quality (X1), service quality (X2), and promotion (X3), influence simultaneou sly on the decision to choose SDIT Mutiara Rahmah Balikpapan. Originality/value: The results of the t-test of the hypothesis indicate that the three independent variables, namely the quality of learning (X1), service quality (X2), and promotion (X3), each partially have a significant effect on the decision to choose SDIT Mutiara Rahmah Balikpapan. Paper type: Research Paper